Vista Angkasa Apartment Management System - Thevaraju, Devi Priya; Zakaria, Zalmiyah; Mohamad Sukri, Khairul Amin; Kasim, Shahreen (SOTVI, 2019)
Vista Angkasa Apartment is one of the oldest apartments in the Bangsar South area, with a total of 8 blocks and consisting of more than 1000 units of houses. Currently, all the transaction related to the maintenance of each apartment is recorded manually. It is very difficult to manage all the data manually and if some information is required urgently then to obtain it also is very difficult. It will not only take a lot of time, but it also increases the chances of errors. Therefore, to solve the issues faced, an apartment management system that allows management staff to view the apartment’s data and tenant’s data as well as maintenance requests, notices and complaints has been developed. It also increases the efficiency and the effectiveness of Vista Angkasa Apartment Management by eliminating the current manual system. Compilation of data can be done easily with just a click of mouse. The methodology that has been applied to develop the system will be Agile with the PHP programming language. The developed system has successfully tested with the real time data at the Vista Angkasa Apartment. Based on the obtained results, the Vista Angkasa Apartment Management System solved the current issues with the management office and tenants.